Big Five personality dimensions and disintegration as antecedents of vertical and horizontal internet privacy concerns - Jošt Bartol; Michael Bošnjak; Vasja Vehovar; Gregor Čehovin; Andraž Petrovčič (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2025)
Given the role that internet privacy concerns (IPCs) have in individuals’ online behaviors, it is essential to understand how personality shapes people’s concerns about privacy online. The five-factor model of human personality—with the Big Five personality dimensions of openness, conscientiousness, extraversion, agreeableness, and neuroticism—has been widely used to study the formation of internet users’ privacy concerns. However, existing literature has investigated only vertical (institutional) IPCs, while there is no corresponding research on horizontal (peer) IPCs. The role of a recently proposed personality trait, disintegration, which captures individuals’ proneness to perceive connections among unrelated phenomena and thus complements existing personality models, has also not been examined yet. This preregistered study addressed these gaps by investigating the associations of the Big Five personality dimensions and the disintegration trait with vertical and horizontal IPCs among internet users. The hypotheses and research questions were addressed through path analysis on a sample of internet users (N = 797) aged 18 years or older, recruited through probability-based sampling (response rate 42%). The results showed that agreeableness was associated with greater vertical IPCs, whereas openness with lower and disintegration with higher horizontal IPCs. The association between disintegration and vertical IPCs was moderated by previous privacy violations. The findings suggest that personality traits have different associations with vertical and horizontal IPCs, warranting further investigation of the role of the disintegration trait in individuals’ online privacy perceptions and behaviors.